A cloning method for caspase substrates that uses the yeast two-hybrid system: Cloning of the antiapoptotic gene gelsolin - Kamada, Shinji (The National Academy of Sciences, 1998)
Caspase-mediated proteolysis is a critical and central element of the apoptotic process; therefore, it is important to identify the downstream molecular targets of caspases. We established a method for cloning the genes of caspase substrates by two major modifications of the yeast two-hybrid system: (i) both large and small subunits of active caspases were expressed in yeast under ADH1 promoters and the small subunit was fused to the LexA DNA-binding domain; and (ii) a point mutation was introduced that substituted serine for the active site cysteine and thereby prevented proteolytic cleavage of the substrates, possibly stabilizing the enzyme–substrate complexes in yeast. After screening a mouse embryo cDNA expression library by using the bait plasmid for caspase-3, we obtained 13 clones that encoded proteins binding to caspase-3, and showed that 10 clones including gelsolin, an actin-regulatory protein implicated in apoptosis, were cleaved by recombinant caspase-3 in vitro. Using the same bait, we also isolated human gelsolin cDNA from a human thymus cDNA expression library. We showed that human gelsolin was cleaved during Fas-mediated apoptosis in vivo and that the caspase-3 cleavage site of human gelsolin was at D(352) of DQTD(352)G, findings consistent with previous observations on murine gelsolin. In addition, we ascribed the antiapoptotic activity of gelsolin (which we previously reported) to prevention of a step leading to cytochrome c release from the mitochondria into the cytosol. Our results indicate that this cloning method is useful for identification of the substrates of caspases and possibly also of other enzymes.